2014
DOI: 10.1186/1471-2407-14-517
|View full text |Cite
|
Sign up to set email alerts
|

Survival disparities in Australia: an analysis of patterns of care and comorbidities among indigenous and non-indigenous cancer patients

Abstract: BackgroundIndigenous Australians have lower overall cancer survival which has not yet been fully explained. To address this knowledge deficit, we investigated the associations between comorbidities, cancer treatment and survival in Indigenous and non-Indigenous people in Queensland, Australia.MethodsA cohort study of 956 Indigenous and 869 non-Indigenous patients diagnosed with cancer during 1998–2004, frequency-matched on age, sex, remoteness of residence and cancer type, and treated in Queensland public hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 32 publications
2
66
1
Order By: Relevance
“…18,23 The observed survival disparity is not unique to LN as it is also seen in IA patients with cancer or receiving renal replacement therapy. [24][25][26][27] The fact that LN class and renal activity index or serological disease measures were not predictive of renal survival strongly suggests that factors other than histological LN severity contribute to this poor renal prognosis. We did not study the extent of comorbidity as it was outside the main scope of our paper, but our results indicate that further investigation is needed to determine the exact role of LN and comorbid conditions in this context.…”
Section: Discussionmentioning
confidence: 99%
“…18,23 The observed survival disparity is not unique to LN as it is also seen in IA patients with cancer or receiving renal replacement therapy. [24][25][26][27] The fact that LN class and renal activity index or serological disease measures were not predictive of renal survival strongly suggests that factors other than histological LN severity contribute to this poor renal prognosis. We did not study the extent of comorbidity as it was outside the main scope of our paper, but our results indicate that further investigation is needed to determine the exact role of LN and comorbid conditions in this context.…”
Section: Discussionmentioning
confidence: 99%
“…9,11 In brief, all Indigenous women, older than 18 years, residing in Queensland, and diagnosed with a gynecologic cancer between 1998 and 2004 were identified via the Queensland Cancer Registry or the Queensland public hospitals. Those who had at least 1 public hospital attendance related to their diagnosis were included.…”
Section: Methodsmentioning
confidence: 99%
“…5 A South Australian study reported higher relative risk of death among Indigenous women than non-Indigenous women with cervical cancer (2.14 [95% CI, 1.17Y3.92]), 4 and a Western Australian study reported higher relative risk of death among Indigenous women compared with non-Indigenous women with ovarian cancer (HR, 2.18 [95% CI, 1.18Y4.02]). 6 The reasons for poorer survival of gynecologic cancers among Indigenous Australian women is likely to be multifaceted and may include increased late-stage diagnosis, 7 less cancer treatment, 7Y10 higher burden of comorbidities, 10,11 and increased remoteness of residence. 12 There is also evidence that survival differences between Australian Indigenous and non-Indigenous cancer patients are most prominent in the first years following diagnosis.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Primary healthcare (PHC) services have an important role in post-discharge cancer care, and accurate communication between hospitalbased specialists and PHC services is imperative. [17][18][19] Aboriginal and Torres Strait Islander people in Australia (respectfully referred to here as Indigenous Australians) comprise 3% of the total Australian population, 20 and experience socioeconomic and health disparities. [8][9][10][11][12][13] High quality PHC is particularly important for groups who experience disproportionate barriers to access to care; such as ethnic minorities, 14 patients who live in rural 15 and more deprived areas 14,16 and indigenous populations.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] High quality PHC is particularly important for groups who experience disproportionate barriers to access to care; such as ethnic minorities, 14 patients who live in rural 15 and more deprived areas 14,16 and indigenous populations. 22 Compared with mainstream Australia, they experience marked disparities in cancer mortality 23 and survival, 18,19,24 which are largely attributed to being diagnosed later, 18,19,25 receiving less treatment 18,19 and experiencing higher rates of comorbidities. 21 Cancer is the second leading cause of death for Indigenous Australians.…”
Section: Introductionmentioning
confidence: 99%